A study of parathyroid hormone deficiency after total and near total thyroidectomy: its occurrence and time for recovery - Ranjit, Lakshmi; Galagali, J. R.; Singh, I. D.; Ramakrishnan, N.; Nilkanthan, Ajith; Singh, S. K.; K., Manoj (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Parathyroid hormone (PTH) deficiency or hypoparathyroidism occurring after total thyroidectomy is not an uncommon postoperative complication. Patients developing PTH deficiency are likely to develop hypocalcemia if not treated in time. These patients will require immediate injectable followed by oral calcium supplements and activated vitamin D (1, 25-dihydroxycholecalciferol or calcitriol). The incidence of hypoparathyroidism reported in the literature varies between 1% to 37%. The aim of our study was to evaluate parathyroid hormone deficiency and the time taken for recovery of parathyroid function in total and near total thyroidectomy patients. Methods: An observational descriptive study was carried out at a tertiary care center with 50 patients who underwent total or near total thyroidectomy. Exclusion criteria- Patients in whom PTH was found to be below 10 pg/ml or above 65pg/ml preoperatively, those in whom neck dissection was done previously, those with abnormal calcium levels preoperatively and those on calcium replacement preoperatively. Results: 12% of patients developed PTH deficiency following total thyroidectomy, but only 2% continued to have prolonged depression of PTH level. A significant relation between fall in PTH on post op evening was found with the development of hypocalcaemia in the post op period. Conclusions: Immediate post operative PTH can be used as an indicator to predict hypocalcemia in the post operative period in patients undergoing total or near total thyroidectomy.